Analisis Perbedaan Penilaian Dampak Sertifikasi dan Faktor Kritis ISO 9001 terhadap Kinerja Institusi Pendidikan Studi Sekolah Menengah Kejuruan di Jakarta - , Rifki Martin, Drs. Ahmad Jamli M.A. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
ISO 9001 aims to improve the organization's internal performance, increase market share and customer satisfaction. For educational institutions, research is still rarely done to show the impact of ISO 9001 to increase the performance of the institution. This prompted the author to analyze whether the certification of ISO 9001 is really able to encourage educational institutions for improving its performance with the study of vocational schools (SMK) in Jakarta. The research objective is to analyze the differences assessment of the impact of ISO 9001 certification to performance improvement between educator and Management Representative (MR) as well as between the SMK economicalbased (SMEA) and technical-based (STM) and analyze the differences in assessment of the critical factors for performance improvement by educator and MR as well as between the SMEA and STM. Mann-Whitney U test was conducted to determine the significance of the differences of data. The study found that there was no significant difference in assessment between educators and MR on the aspects of ISO 9001 certification that had an impact on performance improvement but there was significant difference between the SMEA and STM assessment in the aspects of ISO 9001 certification on performance improvement. In addition, the study found no significant difference between educator and the MR assessment and between SMEA and STM on the critical factors that contributed to performance improvement.